Carbon Steel Biocorrosion Inhibition by Methanol Extract Gracilaria Edulisin Seawater - Dukalang, Fildzah Istiqomah; Warganegara, Fida Madayanti; Bundjali, Bunbun (West Science Interdisciplinary Studies, 2023)
Biocorossion in terrestrial and marinal habitats has been widely studied including the involvement of sulphate reducing bacteria which are of particular concern in the oil and gas industries. One of the sulphate reducing bacteria that triggers biocorossion is Thiobacillus ferrooxidans. This study examines the effectiveness of Gracilaria edulis macroalgae methanol extract obtained from Sayang Heulang Beach Pamengpeuk District, Garut Regency, West Java as a candidate for carbon steel biocorrosion inhibitors in seawater media. Gracilaria edulis extraction process using Folch extraction method (chloroform: methanol: phosphate buffer, 2: 1: 0.8 (v / v)). Separation of the crude methanol-water phase extract using silica column chromatography G-60 7733 with n-hexane: acetone (8: 2, 5: 5, 2: 8 (v / v)) and methanol p.a. From the results of the analysis using a UV spectrophotometer (190-400 nm) there were five combined fractions (Fraction A-Fraction E). Total content of phenolic compounds (TPC) in crude extracts of methanol-water, fraction C and fraction E respectively (410.77; 285.30; 309.51) (mg/gr GAE). The results of the qualitative test of the ability of biocorrosion inhibition of crude extracts of methanol-water phase, fraction C and fraction E by using commercial nails in solid media incubated for four days showed a decrease in the corrosion intensity on nails. Quantitative tests on the ability of biocorrosion inhibition were carried out using the weight-loss method and the results of quantitative tests showed the corrosion rate of fraction C was 12.14 ± 1.09 mpy and the fraction E was 13.94 ± 1.82 mpy for 2.5% NaCl medium while the corrosion rate of fraction C was 10.73 ± 3.63 mpy and the fraction E was 11.72 ± 0.59 mpy for seawater media. The optimum concentration test results in the inhibition showed the smallest corrosion rate fraction C was found at 0.2 mg / mL TPC levels both in 2.5% NaCl media and seawater media which each had a corrosion rate of 12.91 mpy and 8.09 mpy and the optimum concentration of fraction E was found in TPC levels of 0.4 mg / mL (2.5% NaCl media) with a corrosion rate of 14.32 mpy and TPC levels of 0.1 mg / mL (sea water medium) with a corrosion rate of 12.14 mpy. By using the optimum fraction C concentration, the results showed that the fraction C had the maximum resistance in inhibiting for 8 days (192 hours). Analysis of carbon steel plates using SEM and EDS showed that T. ferrooxidans bacterial cells formed a biofilm layer on the surface of the carbon steel plate with a localized density but mostly dominated the carbon steel plate surface and by the addition of SEM image inhibitors showed the carbon steel plate forming a layer thin that protects the metal surface and decreases the solubility of iron sulfide in water. The test results using EDS devices also detect the presence of sulfur elements and a decrease in the percentage of iron element mass on carbon steel plates without inhibitors.